Lungfishes, like tetrapods, possess a vomeronasal system - Agustín González; Ruth Morona; Jesús M López; Nerea Moreno; Glenn R Northcutt (Frontiers Media S.A., 2010)
The vomeronasal system (VNS) is an accessory olfactory system that in tetrapod vertebrates is composed of specific receptors neurons in the nasal organ and a set of centers in the forebrain that receive and relay the information consecutively towards the hypothalamus. Thus, only in tetrapods the VNS comprises a discrete vomeronasal (Jacobson’s) organ, which contains receptor cells that are morphologically distinct from those of the olfactory epithelium and use different transduction mechanisms. The axons of the vomeronasal receptors in tetrapods project to the accessory olfactory bulb (AOB) in the rostral telencephalon. Secondary vomeronasal connections exist through the medial amygdala to the hypothalamus. Currently, the lungfishes are considered the closest living relatives of tetrapods, based on genetic and molecular data. Here we show that the African lungfish, Protopterus dolloi, has epithelial crypts at the base of the lamellae of the olfactory epithelium that express markers of the vomeronasal receptors in tetrapods. The projections of these crypts allow us to identify an AOB on the lateral margin of the main olfactory bulb. The projections of this AOB reach a region that is topologically, hodologically, and immunohistochemically identical to the medial amygdala and could represent its homolog. Neurons of this putative medial amygdala were demonstrated to project to the lateral hypothalamus, as they do in tetrapods. All these features that lungfishes share with tetrapods indicate that lungfishes have the complete set of brain centers and connections involved in processing vomeronasal information and that these features were already present in the last common ancestor of lungfishes and tetrapods.